The Effectiveness and Practicality of a Novel Barrier Membrane for the Open Window in Maxillary Sinus Augmentation with a Lateral Approach, with Risk Indicators for Bone Graft Displacement and Bone Height Decrease: A Prospective Study in Humans - Yamaguchi, Kikue; Munakata, Motohiro; Sato, Daisuke; Kataoka, Yu; Kawamata, Ryota (Bioengineering (Basel), 2023)
Maxillary sinus augmentation with a lateral approach (MSA) is a well-established treatment. In this prospective study, we evaluated risk factors for postoperative bone graft displacement and reported the clinical application of long-term resorbable L-lactic acid/-caprolactone (PLA/PCL) as a barrier membrane to cover the open window in the lateral wall in MSA. Twenty-four patients underwent MSA according to the relevant criteria; CT data obtained before and 1 week (1 w) and 5–6 months (5 m) post-MSA, bone height changes, bone height reduction rates at 1 w and 5 m post-MSA, bone graft displacement measurements, and risk factors were examined. All patients showed bone height increments (p < 0.005). However, no difference was observed between 1 w and 5 m post-MSA. Bone graft displacement was observed in eight patients; the reduction rate from 1 w to 5 m post-MSA was 8.38% ± 4.88%. Sex, septa, maxillary sinus floor–palatal bone distance, and maxillary sinus floor–maxillary ostium distance were associated with bone graft displacement (p < 0.05). The height from the maxillary sinus floor to the palatal bone and the sinus angle influenced the augmentation degree (p < 0.05). The PLA/PCL membrane is compared favorably with other membranes and may be useful as a barrier membrane for the MSA open window.